Dynamic retinal vessel analysis: flickering a light into the brain - Anna Peterfi; Anna Peterfi; Anna Peterfi; Ana Clara da C. Pinaffi-Langley; Ana Clara da C. Pinaffi-Langley; Zsofia Szarvas; Zsofia Szarvas; Zsofia Szarvas; Mihaly Muranyi; Mihaly Muranyi; Mihaly Muranyi; Zalan Kaposzta; et al. (Frontiers in Aging Neuroscience)
IntroductionGrowing aging populations pose new challenges to public health as the number of people living with dementia grows in tandem. To alleviate the burden of dementia, prodromal signs of cognitive impairment must be recognized and risk factors reduced. In this context, non-invasive techniques may be used to identify early changes and monitor disease progression. Dynamic retinal vessel analysis (DVA) provides an opportunity to measure retinal vasoreactivity in a way that may be comparable to cerebral vasoreactivity, thus providing a window to the brain.MethodsWe conducted a literature search on PubMed and Scopus to identify studies utilizing DVA to describe retinal vasoreactivity in central nervous system diseases and compare it with brain function and structure. We included original papers with full text in English.ResultsWe identified 11 studies, of which most employed a cross-sectional design (91%). Studies on cerebrovascular diseases reported that retinal vasoreactivity decreased in patient populations compared with that of healthy controls. Studies on cognitive impairment and dementia yielded mixed results, at least in part due to high population heterogeneity. There is also evidence for the association between DVA and brain and cognition parameters such as cerebral blood flow velocity, cerebral microvascular diffusivity, and cognitive function score.DiscussionThe reviewed papers on DVA and brain function, despite the mixed results, have demonstrated the relationship between retinal vasoreactivity and cerebrovascular function and cognition. Heterogeneity in study populations, procedures, and analyses make comparisons difficult. Studies with larger sample size, clear description of the population and methods, and standardized DVA analysis are needed to elucidate the eye–brain connection and to enhance the translational and clinical applications of DVA.